Molecular engineering control defects within carbon nitride for optimized co-catalyst Pt induced photocatalytic CO2 reduction and NO2 oxidation reaction. (12th April 2022) - Hayat, Asif; Sohail, Muhammad; Al-Sehemi, Abdullah G.; Alghamdi, Noweir Ahmad; Taha, T.A.; AlSalem, Huda Salem; Alenad, Asma M.; Amin, Mohammed A.; Palamanit, Arkom; Liu, Changkun; Baburao Mane, Sunil Kumar; Nawawi, W.I.; et al.
Abstract: We confirmed a specific copolymerization (molecular doping) method for the covalent integration of 2, 4-dihydroxyoxazole (DHO) monomer within the framework of carbon nitride (CN). The obtained composites xCN/DHO reveal a sophisticated dual-phase photocatalytic activity, which can effectively reduce and oxidize the CO2 and NO2 sources in an aqueous solution and simultaneously performed the oxidation of olefin (CC) in an organic state. This momentous dual state activity is concerned with the lipophilicity elevation from the convolution of oxazole (DHO) monomer within the shell of CN semiconductor. This modulation demonstrates the probability of hydrophobic olefin molecules, escorted in the bulk of CN and associated with the oxidation of hydroxyl radicals (∗OH) caused by photogenerated electrons/holes. In this approach, the olefinic compound allusively consumes the photoinduced electrons/holes through elevated CN/DHO, thus stimulating the entire photocatalytic route. Recent research provides a novel strategy for the production of solar fuels upon organic synthesis via the oxidizing capacity of photoinduced holes within free semiconductors of amphiphilic metals. Likewise, the results of the NO2 photocatalytic reaction demonstrated that molecular doping drastically reduces the oxidative capacity and improves its reducing propensity. More importantly, the CO2 reduction process supervenes into an extreme aggregation of methane (CH4 ) as well as carbon monoxide (CO) in the presence of co-catalyst Pt respectively. The photocatalytic results demonstrate that the copolymerized CN provide the greatest reduction/oxidation potential, which is due to its chemical oxidation phase that causes superior fluctuations in whole performance under solar irradiation. Highlights: Synthesis of oxazole (DHO) based carbon nitride (CN) through molecular engineering. Samples were utilized for photocatalytic CO2 reduction and NO2 oxidation. The momentous activity is concerned towards the convolution of DHO within CN. Samples alter the probability for hydrophobic olefin molecules due to *OH radicals. The reduction/oxidation process happen due to excess of electrons/holes in materials. Graphical abstract: Image 1